A strategic plan for Optimum Healthcare Systems, Inc. - Aclaro, Blesilda B. (Animo Repository, 2001)
The health care financing industry in the country emerged from the need of the population to seek ways of paying the increasing cost of health care brought about by inflation, the high cost of technologies, as well as the unrestricted fees and rate setting by providers. Medicare, now known as PHIC under SSS was the government's effort to answer the needs of the people but its subsidy is not sufficient. Health Maintenance Organization (HMO) arise from the needs of Filipinos of an affordable and efficient health care service. There are about 39 HMO companies offering the same service. Analysis of the Philippine environment and the forces that affects the industry show that there are various opportunities in the industry such as the growing population of the Philippines, the trend of convergence of industries, opportunity to provide health care to middle income people due to lack of supply of public health care and Overseas Filipino Workers being a potential clients. On the other hand, there are also various threat in the industry like the rising cost of health care services, emergence of a new health care model, the continuing economic slowdown and continuing laying-off of workers among others. The HMO business should be financially stable before the entry of Insurance Commission as regulating body to HMO companies. Optimum Healthcare System, Inc. is owned and operated by the Waterous Medical Corporation. The company is part of the conglomerate group of companies of the Santiago's which includes the PT&T, CAPWIRE and Pocketbell. The company is in its 5th year of operation as an HMO company but it has already 50 years of experience in providing health care. Currently, the company is experiencing financial constraints as manifested by their low performance ratio and their sufficient funds. Aside from the financial constraints, the company lacks planning in their projects and as well as the manpower. On the other hand, the strength of the companies lie on their innovativeness in providing service like in their quality circle, Optimum Webpage and their 24 Hour Customer Hotline. Based on opportunities and threats present in the industry and the company's strength and weakness, the proposed generic strategy if differentiation. Furthermore, the specific corporate strategies of the company are synergism, geographic expansion, product development, developed E-commerce for Optimum Website and the Health Care to the Optimum Strategy.